A new dynamic fluid‐kinetic model for plasma transport within the plasmasphere. Issue 10 (15th October 2015) - Wang, Yan; Tu, Jiannan; Song, Paul
Abstract: A new dynamic fluid‐kinetic model is developed for investigating the plasma transport along a closed magnetic flux tube in the plasmasphere by coupling the field line interhemispheric plasma (FLIP) model with a generalized semikinetic (GSK) model. The coupling is achieved via an overlapped transition region (800 km–1100 km altitude) in each of the hemispheres. The flux tube is allowed to move both radially away from, toward, and azimuthally around the Earth. In addition to H +, ion species O + and He + are for the first time treated as simulation particles in a numerical model of the plasmasphere. The simulation particles are subjected to the field‐aligned electric field, magnetic mirror force, gravity, centrifugal force, and interspecies and intraspecies Coulomb collisions. The plasmaspheric refilling processes as an application of the model are studied. The simulation results show that the behaviors of O + ions are substantially different from those of H + and He + ions. Key Points: A multispecies dynamic fluid‐kinetic model for plasma transport is developed Effects of the flux tube convection are included in the model Heavy oxygen ions demonstrate different behaviors in the plasmasphere refilling